Influence of Human Resource Quality and Budget Quality on Local Financial Performance: The Mediating Role of Local Management Information System - Hasmin Joko; Abd Rahman Kadir; Aini Indrijawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
In the realm of an increasingly complex global economy, local governments grapple with multifaceted challenges and opportunities in resource and financial management. This study delves into the pivotal aspects of human resource quality (HRQ) and budget quality and their profound influence on local financial performance within the context of Buton Selatan Regency. The investigation unveils that HRQ significantly bolsters financial performance, offering a cornerstone for adept resource management and growth. Similarly, the study underscores the potency of budget quality in steering local financial performance, emphasizing the significance of well-structured budgets aligned with developmental priorities. Moreover, the Local Government Management Information System (LG-MIS) emerges as a vital intermediary, mediating the relationship between HRQ, budget quality, and financial performance. While the direct impacts of HRQ and budget quality stand out, the LG-MIS reinforces these associations, facilitating transparent, efficient, and data-driven financial management. Collectively, these findings illuminate pathways for local governments to enhance their financial standing, emphasizing the interplay between HRQ, budget quality, and the pivotal role of LG-MIS in achieving sustainable financial performance.